Penerapan Prinsip Preventive In Action Dalam Menanggulangi Sampah di Kawasan Pasar Kud Kota Tanjungpinang: Penerapan Prinsip Preventive In Action Dalam Menanggulangi Sampah di Kawasan Pasar - Tri Cahyo Purnomo, Armando; Puspitaria Gulo, Septi; Permatasari, Nilam; Irman, Irman (Mendapo: Journal of Administrative Law, 2023)
Waste management is a challenge that is always faced by every region, including Tanjungpinang City. The rubbish that accumulates on land and sea coasts is increasing every day, the Tanjungpinang City Environmental Service noted that every day Tanjungpinang City has 90-93 tons of household waste and similar household waste, but this figure is the number transported by Integrated Waste Management Site officers to the landfills so The amount of untransported waste that has accumulated in several places may be much higher than expected, this of course draws attention to how the current regulations are working to accommodate the waste problem. Through the principle of prevention in action, the author wants to examine the application of this principle to the implementation of policies regarding waste management. With the research method used, namely Normative Juridical and a research approach through a statutory approach (Statue Approach) and a conceptual approach (Conceptual Approach), the results of this research show the weak application of the preventive in action principle in waste management policies and things that happen in the field.